Technological Gap in Pomegranate Cultivation - Vishnugouda, J.P. Sharma, Premlata Singh (Indian Journal of Extension Education, 2022)
Pomegranate is an export oriented crop and the pomegranates from Karnataka enjoy good market in European Union and the Gulf countries. Over 40 per cent of the crop was exported to these countries. Karnataka occupies first position in export of Pomegranate exports by leading Maharashtra State. About 250 tons of pomegranate were exported from the small area of Kustagi and Yelburga tehsils and volume of trade was in the tune of Rs.8.50 crores Net Profit - Rs.3.75 lakhs to Rs.5.00 lakhs per hectare (8000 – 10700 ); in some cases, it has crossed Rs.6.25 lakhs per hectare (13400 ). However in case of Pomegranate growing areas in India, it is observed that because of some constrains, farmers are not realizing the potential yield and quality because the gap in the adaption of recommended technologies. This study attempts to investigate the technological gap prevailing in the cultivation of better quality pomegranates.. This paper summarizes the present cultivation practices followed by the farmers and prevailing gap in technologies like land preparation and planting, nutrient management, water management etc. and provides suggestions for needed research and promotion of policies to reduce the technological gap in the cultivation of better quality pomegranates.